The heart's eye : emotional influences in perception and attention - Niedenthal, Paula M.; Kitayama, Shinobu (Academic Press, 1994)
Recent years have seen a great deal of attention directed towards the so-called "warm-look," investigating how "cold" cognition and "hot" affect intermingle in perception and decision processes. Following in this vein, this book discusses conceptual models and research findings with respect to how affect influences non-conscious processing. The book is divided into two sections: the first on affect and perception, the second on affect and attention, with discussants bringing each section into a cohesive whole